A cross-sectional study of psychache and coping strategies and therapeutic approaches among Palestinian university students during the Gaza Israeli war - Suheir S. Sabbah; Zaid Yacoub; Hamzeh Yacoub; Rita Yacoub; Ronald R. Holden (Scientific Reports)
Abstract The prolonged Gaza-Israeli war has profoundly impacted the psychological well-being of Palestinian university students, manifesting in elevated levels of psychache—an intense psychological pain marked by despair, humiliation, and helplessness. Despite its established link to suicidal ideation, the relationship between psychache and coping strategies during wartime remains underexplored. This study aims to assess the prevalence and severity of psychache among Palestinian university students in the West Bank during the Gaza-Israeli war, and to identify the coping strategies employed. A cross-sectional study was conducted with 556 participants from various universities in the West Bank using convenience sampling method. Data were collected via online questionnaires, including the Psychache Scale, Orbach and Mikulincer Mental Pain Scale, and Coping Strategies Questionnaire. Descriptive statistics, t-tests, and ANOVA were used to analyze the data. The findings revealed that 10.1 to 13.5% of students experienced high psychache levels, while 38.8 to 41.2% displayed moderate levels. Factors such as marital status and study year were significantly related to psychache levels. The most prevalent coping strategy was diversion followed by reinterpreting, with catastrophizing being the least used. Psychache was positively correlated with maladaptive coping strategies, particularly catastrophizing (r = 0.69, p < 0.01). The study underscores the critical need for targeted mental health interventions among university students during war situations. Enhanced coping strategies and mental health support tailored to students’ demographics and psychosocial context are essential for mitigating the impact of war on psychological well-being.